New insights for creative art processes. Collaboration and experimentation with contemporary artists - Fuentes Duran, Eva Fuentes Duran Mariana; Amor Garcia, Rita Lucía; Soriano Sancho, María Pilar (Ge-conservacion, 2017)
The artists’ idea of exploration in new creative fields frequently triggers the collaboration between artists and other professionals. Understanding the experimentation which comes from it is the art restorers and specialists’ main duty, as they are forced to establish new standards and increase their knowledge on the use of new materials. Consequently, the communication between artists and restorers is frequent nowadays in the form of interviews but also with practical collaborations. This paper tries to show how productive collaborations can be for artists during the creative process in terms of production and possibilities, and for restorers, because this would be the best way to learn about the art concept and its materiality, which will be helpful for the artwork’s future conservation.